(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Production outsourcing is the delegation of one or more stages, and sometimes the entire production cycle, to enterprises of other companies. The use of any external sources to achieve certain goals. If it concerns directly the production process, then in this case we are talking about production outsourcing.